Deletion of running-induced hippocampal neurogenesis by irradiation prevents development of an anxious phenotype in mice - Fuß, Johannes; Ben Abdallah, Nada M.-B.; Hensley, Frank W.; Weber, Klaus-Josef; Hellweg, Rainer; Gass, Peter (PLOS ONE, 2010)
Recent evidence postulates a role of hippocampal neurogenesis in anxiety behavior. Here we report that elevated levels of neurogenesis elicit increased anxiety in rodents. Mice performing voluntary wheel running displayed both highly elevated levels of neurogenesis and increased anxiety in three different anxiety-like paradigms: the open field, elevated O-maze, and dark-light box. Reducing neurogenesis by focalized irradiation of the hippocampus abolished this exercise-induced increase of anxiety, suggesting a direct implication of hippocampal neurogenesis in this phenotype. On the other hand, irradiated mice explored less frequently the lit compartment of the dark-light box test irrespective of wheel running, suggesting that irradiation per se induced anxiety as well. Thus, our data suggest that intermediate levels of neurogenesis are related to the lowest levels of anxiety. Moreover, using c-Fos immunocytochemistry as cellular activity marker, we observed significantly different induction patterns between runners and sedentary controls when exposed to a strong anxiogenic stimulus. Again, this effect was altered by irradiation. In contrast, the well-known induction of brain-derived neurotrophic factor (BDNF) by voluntary exercise was not disrupted by focal irradiation, indicating that hippocampal BDNF levels were not correlated with anxiety under our experimental conditions. In summary, our data demonstrate to our knowledge for the first time that increased neurogenesis has a causative implication in the induction of anxiety.
Gesehen am 24.07.2023